The Peruvian Miracle: Good luck or good policies? - Mendoza, Waldo (2013)
The Peruvian economy has performed extraordinarily over the last 10 years. The 2012 per capita GDP is 66 percent above that of 2002, and more than double its 1992 level. In a long term perspective, the cumulative growth of GDP per capita recorded in the last 10 years has been the strongest since 1900. This is the «Peruvian miracle». This paper aims to find the determinants of the Peruvian miracle. In theory, countries’ macroeconomic performance can be determined by two factors: i) the «good (bad) luck effect» that relates to the international context, which may be favorable or unfavorable, and ii) the «good (bad) policies effects», associated with short-term macroeconomic policies or structural reforms,which are policies that alter the current development model. The hypothesis of this work is that the Peruvian miracle of the last 10 years has much to do with good luck, and, in part, with good short-term macroeconomic policies.